What is a Contemporary Human Ecology - Siniarska, Anna; Wolański, Napoleon (Studia Ecologiae et Bioethicae, 2003)
Human ecology is a synthetic transdisciplinary science concerned with human life and culture as a dynamic component of ecosystems. Human ecology (HE) synthesizes parts of the knowledge of several classical disciplines in a specific way. The essence of HE is the interaction between humans and the total environment. While the whole idea of HE is originated in anthropology, the first time the term .human ecology" was used in geography and next in sociology. Historically, in its monodisciplinary stage of development, the problems of several classical disciplines related to man and environment were called human ecology. The next stage was the multidisciplinary state, related to IBP (International Biological Programme), presenting a patchwork of information without syntheses. Contemporary HE offers more than a patchwork of knowledge and is based on system theory. In human ecology, human evolution and ontogeny are understood as processes of adaptation and adjustment to the environment. HE may be considered to have two parallel foci: an academic HE as a scientific discipline, and an action-oriented HE (environmental engineering, preservation, education, and health protection against environmental deterioration). In HE several divisions and research perspectives may be defined: 1. Philosophical problems of HE; 2. Social and biological problems of human-environment; 3. Environmental problems of human biology and 4. Cultural adaptive behavior.